Ulcère de cornée chronique révélant un syndrome de Parry-Romberg: à propos d´un cas - Maroufi, Sara El (Pan Afr Med J, 2021)
Parry-Romberg´s syndrome is a rare clinical entity characterized by progressive hemifacial atrophy associated with several systemic manifestations including ophthalmologic, neurologic, maxillofacial symptoms whose treatment should be multidisciplinary. We here report a case of Parry-Romberg´s syndrome diagnosed in a patient referred for management of chronic corneal ulcer following hypoesthesia, characterized by rare and difficult-to-treat features.